2016
DOI: 10.1177/0047287516663650
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Value-Creation on Consumer-Based Destination Brand Equity

Abstract: The present work examines the competitive strategies of tourist destinations and proposes that value-creation among tourists during their entire experience of a destination (before, during, and after their stay) is an antecedent of increased destination brand equity. This value-creation is conceptualized and measured from the service-dominant logic perspective. The research objective is achieved by (a) identifying the dimensions of customer-based destination brand equity and tourist value-creation; (b) validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
104
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(115 citation statements)
references
References 81 publications
6
104
0
5
Order By: Relevance
“…Yet, other dimensions are added into measurement, such as brand associations (Im et al, 2012) and brand assets (Kladou & Kehagias, 2013). Therefore, this study attempts to confirm suggested dimensions by Jamilena et al (2016) as a significant measurement of customer-based destination brand equity and the application of the dimensions in case study. In this study, customer-based destination brand equity is measured by five dimensions suggested, which are destination brand awareness, destination brand Image, destination brand quality, destination brand value, and destination brand loyalty.…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…Yet, other dimensions are added into measurement, such as brand associations (Im et al, 2012) and brand assets (Kladou & Kehagias, 2013). Therefore, this study attempts to confirm suggested dimensions by Jamilena et al (2016) as a significant measurement of customer-based destination brand equity and the application of the dimensions in case study. In this study, customer-based destination brand equity is measured by five dimensions suggested, which are destination brand awareness, destination brand Image, destination brand quality, destination brand value, and destination brand loyalty.…”
Section: Introductionmentioning
confidence: 92%
“…(Gartner et al, 2011). Thus, the dimensions to measure customer-based destination brand-equity purpose in this research, based on Jamilena et al (2016) are classified into five dimensions: awareness, quality, image, loyalty, and value. Each of the dimensions are explained below.…”
Section: Customer's Based Destination Brand Equitymentioning
confidence: 99%
See 3 more Smart Citations